Algae extract-based nanoemulsions for photoprotection against UVB radiation: an electrical impedance spectroscopy study - Aura Rocío Hernández; Lady Sepulveda; Yoshie Hata; Leonardo Castellanos; Sebastian Björklund; Tautgirdas Ruzgas; Marcela Aragón (Scientific Reports)
Abstract Skin cancer is one of the most common types of cancer worldwide, with exposure to UVB radiation being a significant risk factor for its development. To prevent skin cancer, continuous research efforts have focused on finding suitable photoprotective ingredients from natural sources that are also environmentally friendly. This study aimed to develop oil-in-water photoprotective nanoemulsions containing marine macroalgae extract. A Box–Behnken experimental design was used to identify the most promising formulation composition, resulting in optimal physical properties. These properties, including droplet size, polydispersity index (PDI), and zeta potential, were evaluated using dynamic light scattering (DLS). To assess the photoprotection capacity of the formulations, electrical impedance spectroscopy (EIS) was employed to evaluate alterations in the electrical characteristics of excised pig skin membranes placed in Franz cells equipped with a 4-electrode set-up. The final composition of the nanoemulsion was caprylic/capric triglycerides 4%, Macrogolglycerol ricinoleate 30%, and algae extract 1%. The nanoemulsions had an average droplet size of 128.5 ± 8.6 nm, a PDI of 0.25 ± 0.06, and a zeta potential of 45.14 ± 0.02 mV. Compared to the control group, the photoprotective capacity of the oil-in-water nanoemulsions was statistically significant. Specifically, only a 15% reduction in the skin membrane electrical resistance following UVB exposure was observed when the formulation containing algae extract was used, whereas a 50% reduction was observed for the vehicle. In conclusion, this work demonstrates that the developed nanoemulsions based on natural ingredients show promising protective capacity against UVB exposure of the skin.